An in silico study on the anti-diabetic potential of some compounds from the genus Cordyceps - Nguyen, Dai Chau; Nguyen, Cong Kinh; Nguyen Thi, Thanh Hai; Phan, Tu Quy; Nguyen, Vinh Phu; Bui, Quang Thanh; Nguyen, Chi Bao; Ton That, Huu Dat; Nguyen Thi, Ai Nhung (Hue University Journal of Science: Natural Science, 2025)
This study was designed to evaluate the inhibitory potential of nine representative compounds, belonging to the nucleoside, flavonoid, and steroid classes from Cordyceps species, against two protein targets: α-amylase (PDB ID: 4W93) and α-glucosidase (PDB ID: 3W37) by means of an in-silico approach. Molecular docking simulations identified sites 1 and 2 as the optimal sites for ligand interaction with the two respective proteins. The docking results were validated, with RMSD values of less than 2.0 Å for all complexes. Compound C3 was identified as the most potent inhibitor for protein 4W93, while C2 was the most effective against protein 3W37. According to Lipinski’s rule of five, all compounds exhibited favourable “drug-likeness” characteristics, and the pharmacokinetic and toxicological properties of these compounds were further evaluated via ADMET parameter predictions. The complexes, C3-4W93 and C2-3W37, were selected for molecular dynamics simulations. The two complexes are structurally stable throughout the simulation, and the C3 ligand forms the most favourable and persistent interactions with the 4W93 protein.